Internal audit and risk management in South Africa: adherence to guidance - Coetzee, Philna; Lubbe, Dave (University of the Free State, 2011)
English: governance. Sound corporate governance requires, among other things, that the board should ensure that there is an effective risk-based internal audit. The importance of internal audit within risk management and assisting the board of directors in this regard cannot be over-emphasised. The formal guidance of the IIA should be a starting point for internal auditors when performing their duties. Further applicable and comprehensive guidelines and legislation in this regard are urgently needed. This article aims to obtain input from heads of prominent internal audit functions within the private and public sectors on the role of internal auditing in the management of risk.

Afrikaans: governance. Sound corporate governance requires, among other things, that the board should ensure that there is an effective risk-based internal audit. The importance of internal audit within risk management and assisting the board of directors in this regard cannot be over-emphasised. The formal guidance of the IIA should be a starting point for internal auditors when performing their duties. Further applicable and comprehensive guidelines and legislation in this regard are urgently needed. This article aims to obtain input from heads of prominent internal audit functions within the private and public sectors on the role of internal auditing in the management of risk.
Keywords: Risk management; Corporate governance; Guidelines